Composite positive electrode material of solid electrolyte epitaxial coating as well as preparation method and application of composite positive electrode material
By combining the high-conductivity chloride solid electrolyte epitaxial layer with configuration entropy ultra-high nickel positive electrode material, the problems of irreversible phase change and structural degradation of ultra-high nickel positive electrode material during the cycle are solved, and the electrochemical stability and rate performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411772339.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-04
AI Technical Summary
Existing ultra-high nickel positive electrode materials are prone to irreversible phase change and structural degradation during the cycle, which affects their electrochemical properties.
The high conductivity chloride solid electrolyte epitaxial layer is combined with the configuration entropy ultra-high nickel cathode material, and the composite cathode material is prepared through co-precipitation, wet ball milling, freeze-drying and high-temperature calcination, which reduces interface reactions and microcracks and enhances Li+ diffusion kinetics.
It significantly suppresses the deterioration of the interface structure of the positive electrode material under the charging voltage, improves the electrochemical stability and rate performance of the battery, and extends the life of the material.
Smart Images

Figure CN119560540A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery positive electrode materials, and in particular relates to a composite positive electrode material of a solid electrolyte epitaxial coating, a preparation method and an application thereof. Background Art
[0002] In recent years, with the gradual increase in the popularity of electric vehicles, consumers' expectations for the endurance of electric vehicles have also increased. Improving the performance of power batteries mainly depends on the core indicator of energy density, and the energy density of positive electrode materials will directly affect the comprehensive performance of power batteries. In order to meet the needs of long-term driving of electric vehicles, the energy density of power batteries needs to reach more than 400Wh / kg, and the existing positive electrode materials cannot achieve this goal. It is necessary to develop ultra-high nickel positive electrode materials with high specific capacity and energy density to store more electricity and achieve longer driving range. Among them, all-solid-state batteries are regarded as the most promising power source for the next generation of electric vehicles because of their higher energy density and better safety performance than traditional lithium-ion batteries. Based on this, researchers plan to apply ultra-high nickel positive electrode materials in solid-state batteries to further improve the endurance of electric vehicles.
[0003] Although ultra-high nickel cathode materials have the potential to improve the energy density of lithium-ion batteries, they will still encounter problems such as irreversible phase change and structural degradation during the cycle, which will ultimately affect their electrochemical performance. Researchers use element doping and coating modification methods to suppress the strain and surface residual lithium problems that occur during the cycle, which is an effective means to synthesize composite cathode materials with higher capacity and more stable cycles. For example, Chinese invention patent CN118315572A discloses a composite solid electrolyte and its solid-state battery, including an inner oxide solid electrolyte and an outer sulfide solid electrolyte coated on the surface of the cathode material, which has the advantages of smaller particle size and larger specific surface area, and improves the side reactions and antioxidant capacity at the cathode interface, but its preparation process is too complicated and requires multiple ball milling heating for synthesis. Invention patent CN117673297A discloses a high nickel cathode material coated with a Zr / Ga doped halide solid electrolyte and a preparation method thereof, which uses a method of Zr / Ga dual doping and halide solid electrolyte coating the cathode material to improve the material's cycle stability and rate performance, but its discharge specific capacity does not have an advantage.
[0004] Therefore, it is of great significance to select an appropriate modification process and screen out solid electrolytes with high conductivity and high stability to construct the interface layer of the positive electrode material. Summary of the invention
[0005] The purpose of the present invention is to solve the problems faced by ultra-high nickel positive electrode materials, and to utilize the coupling effect of high conductivity solid electrolyte epitaxial layer and configuration entropy composite positive electrode material to effectively reduce interface reaction and microcracks, and enhance Li + Diffusion dynamics, the composite positive electrode material of the solid electrolyte epitaxial coating provided by the present invention helps to alleviate the disorder degree and inherent strain of the positive electrode material through the chloride solid electrolyte epitaxial coating, enhance the consistency and interface compatibility between the electrode and the electrolyte, and improve the configuration entropy of the ultra-high nickel positive electrode material LiNi x Co y Mn 1-x-y O 2 electrochemical properties, thereby constructing a composite positive electrode material with high stability and long life.
[0006] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:
[0007] In a first aspect, the present invention provides a composite positive electrode material of a solid electrolyte epitaxial coating, comprising an inner positive electrode active material and an epitaxial layer coated on the outside of the inner positive electrode active material;
[0008] The inner positive electrode active material is a configurational entropy ultra-high nickel positive electrode material, and the general formula of the configurational entropy ultra-high nickel positive electrode material is LiNi x Co y M 1-x-y O 2 ;
[0009] Among them, 0.95≤x<1, 0<y≤0.05;
[0010] M is one or more of Mn, Mg, Y, W, and Zr;
[0011] The material of the epitaxial layer is a chloride solid electrolyte, and the general formula of the chloride solid electrolyte is Li a XCl 6 , 2.7≤a≤3;
[0012] Wherein, X is one or more of In, Y, Ta, and Zr.
[0013] Furthermore, the mass ratio of the epitaxial layer to the inner layer positive electrode active material is 0.5:100 to 5:100.
[0014] Furthermore, the configurational entropy ultra-high nickel cathode material is a spherical particle;
[0015] The particle size of the configurational entropy ultra-high nickel positive electrode material is 5 to 10 μm.
[0016] In a second aspect, the present invention provides a method for preparing a composite positive electrode material of a solid electrolyte epitaxial coating, the preparation method comprising the following steps:
[0017] S1. According to the general formula of the configurational entropy ultra-high nickel positive electrode material, nickel salt, cobalt salt and metal salt are weighed to prepare a metal salt solution, and sodium hydroxide solution and ammonia solution are prepared. The metal salt solution, sodium hydroxide solution and ammonia solution are transported to a reactor under the protection of a nitrogen atmosphere in a parallel flow manner for co-precipitation reaction to prepare a reaction slurry. The prepared reaction slurry is filtered, washed with water and dried to obtain a precursor powder. The precursor powder and lithium hydroxide are weighed and mixed evenly, placed in a tube furnace, and sintered at high temperature in an oxygen atmosphere to obtain the configurational entropy ultra-high nickel positive electrode material LiNi x Co y M 1-x-y O 2 ;
[0018] S2. According to the general formula of chloride solid electrolyte, weigh a metal chloride salt, mix the weighed metal chloride salt and the configurational entropy ultra-high nickel positive electrode material by wet ball milling, evacuate and place after mixing evenly to prepare a mixed solution, and freeze-dry the mixed solution to prepare a mixed material;
[0019] S3. The mixed material is calcined at high temperature under an argon atmosphere to prepare a composite positive electrode material.
[0020] Furthermore, in step S1, the metal salt is any one or more of manganese salt, magnesium salt, yttrium salt, tungsten salt and zirconium salt mixed in any proportion.
[0021] Furthermore, in step S1, during the coprecipitation reaction, the reaction temperature is 45-65°C, the concentration of the metal salt solution is 1.5-2 mol / L, the feed rate of the metal salt solution is 100-200 mL / h, the concentration of the sodium hydroxide solution is 7-10 mol / L, the feed rate of the sodium hydroxide solution is 120-180 ml / h, the concentration of the ammonia solution is 4-6 mol / L, the feed rate of the ammonia solution is 40-60 ml / h, the stirring rate in the kettle is 500-850 rpm, the pH value in the kettle is 10.8-11.4, and the coprecipitation reaction time is 15-20 h.
[0022] Furthermore, in step S1, during the coprecipitation reaction, the reaction temperature is 55°C, the metal salt solution feed rate is 200 mL / h, the stirring rate in the kettle is 800 rpm, the pH value in the kettle is 11.2, and the coprecipitation reaction time is 20 h.
[0023] Furthermore, the metal chloride salt is any one or more of lithium chloride, indium chloride, yttrium chloride, tantalum chloride and zirconium chloride mixed in any proportion.
[0024] Furthermore, in step S2, during the wet ball milling mixing process, the wet ball milling time is 1 to 8 hours, and the ball milling rate is 150 to 500 rpm;
[0025] During the wet ball milling mixing process, the grinding medium of the wet ball milling is ethanol, and the ratio of the total mass of the metal chloride and the configurational entropy ultra-high nickel positive electrode material to the mass of the ethanol is 1:(0.5-2.0);
[0026] During the vacuuming and placing process, the vacuuming and placing time is 10 to 30 minutes;
[0027] During the freeze-drying process, the freeze-drying time is 6 to 10 hours and the freeze-drying temperature is -20°C to -40°C.
[0028] Furthermore, in step S3, during the high-temperature calcination process, the high-temperature calcination temperature is 250-450° C., the high-temperature calcination time is 4-8 hours, and the heating rate is 2-5° C. / min.
[0029] In a third aspect, the present invention provides an application in a battery of a composite positive electrode material prepared by the preparation method of the composite positive electrode material of a solid electrolyte epitaxial coating provided in an embodiment of the first aspect of the present invention or the composite positive electrode material of a solid electrolyte epitaxial coating provided in an embodiment of the second aspect of the present invention.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The present invention provides a composite positive electrode material of a solid electrolyte epitaxial coating, which is obtained by steps of hydroxide coprecipitation, wet ball milling, freeze drying and lithiation high temperature calcination.
[0032] 2. In the composite positive electrode material provided by the present invention, the epitaxial layer Li a XCl 6 Chloride-based amorphous electrolytes have high conductivity comparable to that of liquid electrolytes and exhibit good high-voltage stability. They can be co-precipitated with hydroxides and sintered at high temperatures to prepare LiNi, a high-entropy nickel cathode material. x Co y M 1-x-y O 2 Matching significantly inhibits the structural deterioration at the interface with the positive electrode material under the charging voltage, and improves the electrochemical stability of the battery through the synergistic effect of interface compatibility and configuration entropy effect. A stable electrode-electrolyte interface is further formed. This strong interface can enhance the charge transfer kinetics and improve the discharge capacity and rate performance of the material.
[0033] 3. The preparation method provided by the present invention is simple, easy to implement, low-cost, and can be synthesized on a large scale, and can be expanded and applied to the synthesis of other energy storage materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0035] Figure 1 This is a FESEM image of the composite positive electrode material of the solid electrolyte epitaxial coating obtained in Example 1 of the present invention; Figure 1 In the figure, (a) is a FESEM image of the composite positive electrode material of the solid electrolyte epitaxial coating obtained in Example 1, with a scale of 10 μm; (b) is a FESEM image of the composite positive electrode material of the solid electrolyte epitaxial coating obtained in Example 1, with a scale of 1 μm.
[0036] Figure 2 The FESEM images of the composite positive electrode materials of the solid electrolyte epitaxial coatings obtained in Examples 2 and 4 of the present invention; Figure 2 In the figure, (a) is a FESEM image of the composite positive electrode material of the solid electrolyte epitaxial coating obtained in Example 2, with a scale of 2 μm; (b) is a FESEM image of the composite positive electrode material of the solid electrolyte epitaxial coating obtained in Example 4, with a scale of 2 μm.
[0037] Figure 3 It is a first cycle charge and discharge curve diagram of a battery assembled with the composite positive electrode material of the solid electrolyte epitaxial coating of Examples 1 to 4 of the present invention and the configurational entropy type ultra-high nickel positive electrode material of Comparative Examples 1 to 2. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] The following are specific examples. In the following examples, unless otherwise specified, all raw materials can be obtained from commercial sources.
[0040] Example 1
[0041] This embodiment provides a method for preparing a composite positive electrode material, the preparation method comprising the following steps:
[0042] S1: First, based on the hydroxide coprecipitation reaction, the sulfates of nickel, cobalt, manganese, magnesium, yttrium and zirconium are used as reaction raw materials in a certain proportion to prepare a metal salt solution, a sodium hydroxide solution and an ammonia solution as a precipitant and a complexing agent, respectively. The above three solutions (metal salt solution, sodium hydroxide solution and ammonia solution) are transported to a reactor under the protection of a nitrogen atmosphere in a parallel flow manner for reaction. During the reaction, the reaction temperature is controlled to be 55°C, the concentration of the metal salt solution is 2 mol / L, the feed rate is 200 mL / h, and the sodium hydroxide solution is The concentration is 10 mol / L and the feeding rate is 180 ml / h, the concentration of ammonia solution is 6 mol / L and the feeding rate is 60 ml / h, the stirring rate in the kettle is 800 rpm, the pH value in the kettle is 11.2, and the coprecipitation reaction time is 20 h; the reaction slurry is then filtered, washed with water and dried to obtain a precursor powder; 20 g of the precursor powder and 9.6 g of lithium hydroxide are weighed and mixed evenly in a tubular furnace, and sintered at 720 ° C for 15 h in an oxygen atmosphere to obtain a configurational entropy ultra-high nickel positive electrode material LiNi 0.95 Co 0.01 Mn 0.01 Mg 0.01 Y 0.01 Zr 0.01 O 2 ;
[0043] S2: Weigh 0.21g lithium chloride, 0.306g indium chloride, 0.039g yttrium chloride, 0.03g tantalum chloride and 0.021g zirconium chloride and 20g configurational entropy ultra-high nickel positive electrode material LiNi 0.95 Co 0.01 Mn 0.01 Mg 0.01 Y 0.01 Zr 0.01 O 2 Put it into a ball mill jar, add 20 ml of ethanol and perform wet ball milling, the ball milling rate is 200 rpm, and the ball milling time is 4 hours; after mixing evenly, first vacuumize and place for 10 minutes, then freeze-dry, set the freeze-drying time to 8 hours, and the freezing temperature to -20°C; disperse the chloride salt in the epitaxial layer of the configurational entropy ultra-high nickel positive electrode material to obtain a mixed material;
[0044] S3: The mixed material in S2 was calcined at high temperature under argon atmosphere at a temperature of 300°C, a calcination time of 5 h, and a heating rate of 2°C / min to finally obtain a solid electrolyte Li 2.85 In 0.8 Y 0.1 Ta 0.05 Zr 0.05 Cl 6 Composite cathode materials with epitaxial coating.
[0045] like Figure 1 As shown, the solid electrolyte Li prepared in Example 1 of the present invention 2.85 In 0.8 Y 0.1 Ta 0.05 Zr 0.05 Cl 6 The FESEM image of the composite cathode material of the epitaxial coating shows that the material is spherical in shape with a particle size of 5 to 10 μm and has Li 2.85 In 0.8 Y 0.1 Ta 0.05 Zr 0.05 Cl 6 Small particles grow on its surface as an epitaxial coating.
[0046] Example 2
[0047] This embodiment provides a method for preparing a composite positive electrode material, the preparation method comprising the following steps:
[0048] S1: In this embodiment, step S1 is performed with reference to step S1 in embodiment 1.
[0049] S2: Weigh 0.14g lithium chloride, 0.2g indium chloride, 0.024g yttrium chloride and 0.04g tantalum chloride and 20g configurational entropy ultra-high nickel positive electrode material LiNi 0.95 Co 0.01 Mn 0.01 Mg 0.01 Y 0.01 Zr 0.01 O 2 Put it into a ball mill and add 25 ml of ethanol for wet ball milling. The ball milling rate is 250 rpm and the ball milling time is 5 hours. After mixing evenly, vacuum it and place it for 20 minutes, then freeze-dry it. Set the freeze-drying time to 7 hours and the freezing temperature to -30°C. Disperse the chloride salt in the epitaxial layer of the positive electrode material to obtain a mixed material.
[0050] S3: The mixed material in S2 was calcined at high temperature under argon atmosphere at a temperature of 250°C, a calcination time of 6 h, and a heating rate of 3°C / min to finally obtain a solid electrolyte Li 2.8 In 0.8 Y 0.1 Ta 0.1 Cl 6 Composite cathode materials with epitaxial coating.
[0051] like Figure 2 (a) shows the solid electrolyte Li prepared in Example 2 of the present invention. 2.8 In 0.8 Y 0.1 Ta0.1 Cl 6 FESEM image of the composite cathode material of the epitaxial coating, which is also spherical particles of 5 to 10 μm, with a rough surface and uniform Li 2.8 In 0.8 Y 0.1 Ta 0.1 Cl 6 The epitaxial coating is distributed on its surface.
[0052] Example 3
[0053] This embodiment provides a method for preparing a composite positive electrode material, the preparation method comprising the following steps:
[0054] S1: In this embodiment, step S1 is performed with reference to step S1 in embodiment 1;
[0055] S2: Weigh 0.16g lithium chloride, 0.242g indium chloride and 0.032g yttrium chloride and 20g configurational entropy ultra-high nickel positive electrode material LiNi 0.95 Co 0.01 Mn 0.01 Mg 0.01 Y 0.01 Zr 0.01 O 2 Put it into a ball mill jar, add 30 ml of ethanol and perform wet ball milling, the ball milling speed is 150 rpm, and the ball milling time is 8 hours; after mixing evenly, first vacuum it and place it for 30 minutes, then freeze dry it, set the freeze drying time to 6 hours, and the freezing temperature to -20°C; disperse the chloride salt in the epitaxial layer of the positive electrode material to obtain a mixed material;
[0056] S3: The mixed material in S2 was calcined at high temperature under argon atmosphere at a temperature of 250°C, a calcination time of 6 h, and a heating rate of 2°C / min to finally obtain a solid electrolyte Li 3 In 0.9 Y 0.1 Cl 6 Composite cathode materials with epitaxial coating.
[0057] Example 4
[0058] This embodiment provides a method for preparing a composite positive electrode material, the preparation method comprising the following steps:
[0059] S1: First, based on the hydroxide co-precipitation reaction, the sulfates of nickel, cobalt, manganese, magnesium, yttrium and ammonium tungstate are used as the reaction raw materials in a certain proportion to prepare a metal salt solution, a sodium hydroxide solution and an ammonia solution as the precipitant and a complexing agent respectively, and the above three solutions (metal salt solution, sodium hydroxide solution and ammonia solution) are transported to a reactor under the protection of a nitrogen atmosphere in a parallel flow manner for reaction. During the reaction process, the reaction temperature is controlled to be 55°C, the concentration of the metal salt solution is 2 mol / L, the feed rate is 200 mL / h, and the sodium hydroxide solution is The concentration is 10 mol / L and the feeding rate is 180 ml / h, the concentration of ammonia solution is 6 mol / L and the feeding rate is 60 ml / h, the stirring rate in the kettle is 800 rpm, the pH value in the kettle is 11.2, and the coprecipitation reaction time is 20 h; the above reaction slurry is then filtered, washed with water and dried to obtain a precursor powder; 20 g of the precursor powder and 9.6 g of lithium hydroxide are weighed and mixed evenly in a tubular furnace, and sintered at 720 ° C for 15 h in an oxygen atmosphere to finally obtain the configurational entropy ultra-high nickel positive electrode material LiNi 0.96 Co 0.02 Mn 0.005 Mg 0.005 Y 0.005 W 0.005 O 2 .
[0060] S2: Weigh 0.21g lithium chloride, 0.304g indium chloride, 0.021g yttrium chloride, 0.06g tantalum chloride and 0.014g zirconium chloride and 20g configurational entropy ultra-high nickel positive electrode material LiNi 0.96 Co 0.02 Mn 0.005 Mg 0.005 Y 0.005 W 0.005 O 2 Put it into a ball mill and add 25 ml of ethanol for wet ball milling. The ball milling rate is 500 rpm and the ball milling time is 1 hour. After mixing evenly, vacuum it and place it for 30 minutes, then freeze-dry it. Set the freeze-drying time to 10 hours and the freezing temperature to -40°C. Disperse the chloride salt in the epitaxial layer of the positive electrode material to obtain a mixed material.
[0061] S3: The mixed material in S2 was calcined at high temperature under argon atmosphere at a temperature of 280°C, a calcination time of 6 h, and a heating rate of 4°C / min to finally obtain a solid electrolyte Li 2.75 In 0.8 Y 0.05 Ta 0.1 Zr 0.05 Cl 6 Composite cathode materials with epitaxial coating.
[0062] like Figure 2 (b) shows the solid electrolyte Li prepared in Example 4 of the present invention. 2.75 In 0.8 Y 0.05 Ta 0.1 Zr 0.05 Cl 6 The FESEM image of the composite cathode material with epitaxial coating is composed of finer primary particles, which is caused by the introduction of configurational entropy elements such as Y and W; but the surface of the particles becomes slightly blurred, which may be due to the solid electrolyte epitaxial coating Li 2.75 In 0.8 Y 0.05 Ta 0.1 Zr 0.05 Cl 6 Caused by.
[0063] Comparative Example 1
[0064] This comparative example only includes step S1 in Example 1, and does not include the solid electrolyte epitaxial coating preparation process of S2 and S3 to obtain the configurational entropy ultra-high nickel positive electrode material LiNi 0.95 Co 0.01 Mn 0.01 Mg 0.01 Y 0.01 Zr 0.01 O 2 .
[0065] Comparative Example 2
[0066] This comparative example only includes step S1 in Example 4, and does not include the solid electrolyte epitaxial coating preparation process of S2 and S3 to obtain the configurational entropy ultra-high nickel positive electrode material LiNi 0.96 Co 0.02 Mn 0.005 Mg 0.005 Y 0.005 W 0.005 O 2 .
[0067] Performance Testing
[0068] The composite positive electrode material prepared in the embodiment and the positive electrode material prepared in the comparative example were subjected to performance tests, and the relevant test parameters and test procedures are as follows:
[0069] Electrochemical performance test: The composite positive electrode materials prepared in the above examples 1 to 4 and comparative examples 1 to 2 were mixed and ground evenly with the conductive agent acetylene black and the binder polytetrafluoroethylene in a mass ratio of 9:0.5:0.5, and coated on aluminum foil. Dry at 80°C for 10 hours. A polypropylene film (Celgard 2400) was used as a diaphragm, a metal lithium sheet was used as a counter electrode, and 1 mol / L lithium hexafluorophosphate (LiPF6 ) was used as the electrolyte, and a mixed solution of ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) (1:1:1, v:v:v) was assembled into a lithium-ion half-cell. Electrochemical performance tests were carried out in the voltage window of 2.8-4.35V, including the initial charge and discharge test, charge and discharge rate test and charge and discharge cycle test, as shown in Table 1 and Figure 3 As shown;
[0070] Table 1 Electrochemical performance test results
[0071]
[0072] From Table 1 and Figure 3 It can be seen that the composite positive electrode materials prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 2 are applied to lithium-ion half-cells, and the electrochemical performance thereof is tested. Specifically, the discharge capacity of Examples 1 to 4 is significantly higher than that of Comparative Examples 1 to 2 samples in the first charge and discharge test at a current density of 0.1C, and the charge and discharge tests at current densities of 1C and 2C also show excellent rate performance. As can be seen from Table 1, the 50-cycle capacity retention rates of the composite positive electrode materials prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 2 are 92.7%, 92.5%, 90.6%, 89.4%, 83.6% and 81.4%, respectively. In comparison, the solid electrolyte epitaxial coating Li a XCl 6 The samples of the embodiments show obvious advantages in cycle stability. a XCl 6 Effectively improve the configurational entropy of ultra-high nickel cathode material LiNi x Co y M 1-x-y O 2 Long-term stability and electrochemical performance.
[0073] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0074] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A composite positive electrode material of a solid electrolyte epitaxial coating, characterized in that: It includes an inner positive electrode active material and an epitaxial layer coated on the outer surface of the inner positive electrode active material; The inner positive electrode active material is a configurational entropy ultra-high nickel positive electrode material, and the general formula of the configurational entropy ultra-high nickel positive electrode material is LiNi x Co y M 1-x-y O2; Among them, 0.95≤x<1, 0<y≤0.05; M is one or more of Mn, Mg, Y, W, and Zr; The material of the epitaxial layer is a chloride solid electrolyte, and the general formula of the chloride solid electrolyte is Li a XCl6, 2.7≤a≤3; Wherein, X is one or more of In, Y, Ta, and Zr.
2. The composite positive electrode material of a solid electrolyte epitaxial coating according to claim 1, characterized in that: The mass ratio of the epitaxial layer to the inner layer positive electrode active material is 0.5:100 to 5:
100.
3. The composite positive electrode material of a solid electrolyte epitaxial coating according to claim 1, characterized in that: The configurational entropy ultra-high nickel positive electrode material is a spherical particle; The particle size of the configurational entropy ultra-high nickel positive electrode material is 5 to 10 μm.
4. A method for preparing a composite positive electrode material of a solid electrolyte epitaxial coating according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: S1. According to the general formula of the configurational entropy ultra-high nickel positive electrode material, nickel salt, cobalt salt and metal salt are weighed to prepare a metal salt solution, and sodium hydroxide solution and ammonia solution are prepared. The metal salt solution, sodium hydroxide solution and ammonia solution are transported to a reactor under the protection of a nitrogen atmosphere in a parallel flow manner for co-precipitation reaction to prepare a reaction slurry. The prepared reaction slurry is filtered, washed with water and dried to obtain a precursor powder. The precursor powder and lithium hydroxide are weighed and mixed evenly, placed in a tube furnace, and sintered at high temperature in an oxygen atmosphere to obtain the configurational entropy ultra-high nickel positive electrode material LiNi x Co y M 1-x-y O2; S2. According to the general formula of chloride solid electrolyte, weigh a metal chloride salt, mix the weighed metal chloride salt and the configurational entropy ultra-high nickel positive electrode material by wet ball milling, evacuate and place after mixing evenly to prepare a mixed solution, and freeze-dry the mixed solution to prepare a mixed material; S3. The mixed material is calcined at high temperature under an argon atmosphere to prepare a composite positive electrode material.
5. The method for preparing a composite positive electrode material of a solid electrolyte epitaxial coating according to claim 4, characterized in that: In step S1, the metal salt is any one or more of manganese salt, magnesium salt, yttrium salt, tungsten salt and zirconium salt mixed in any proportion.
6. The method for preparing a composite positive electrode material of a solid electrolyte epitaxial coating according to claim 4, characterized in that: In step S1, during the coprecipitation reaction, the reaction temperature is 45-65°C, the metal salt solution feed rate is 100-200 mL / h, the stirring rate in the kettle is 500-850 rpm, the pH value in the kettle is 10.8-11.4, and the coprecipitation reaction time is 15-20 h.
7. The method for preparing a composite positive electrode material of a solid electrolyte epitaxial coating according to claim 4, characterized in that: The metal chloride salt is any one or more of lithium chloride, indium chloride, yttrium chloride, tantalum chloride and zirconium chloride mixed in any proportion.
8. The method for preparing a composite positive electrode material of a solid electrolyte epitaxial coating according to claim 4, characterized in that: In step S2, during the wet ball milling mixing process, the wet ball milling time is 1 to 8 hours, and the ball milling rate is 150 to 500 rpm; During the wet ball milling mixing process, the grinding medium of the wet ball milling is ethanol, and the ratio of the total mass of the metal chloride and the configurational entropy ultra-high nickel positive electrode material to the mass of the ethanol is 1:(0.5-2.0); During the vacuuming and placing process, the vacuuming and placing time is 10 to 30 minutes; During the freeze-drying process, the freeze-drying time is 6 to 10 hours and the freeze-drying temperature is -20°C to -40°C.
9. The method for preparing a composite positive electrode material of a solid electrolyte epitaxial coating according to claim 4, characterized in that: In step S3, during the high-temperature calcination process, the high-temperature calcination temperature is 250-450° C., the high-temperature calcination time is 4-8 hours, and the heating rate is 2-5° C. / min.
10. Use of a composite positive electrode material of a solid electrolyte epitaxial coating according to any one of claims 1 to 3 or a composite positive electrode material prepared by the preparation method of a composite positive electrode material of a solid electrolyte epitaxial coating according to any one of claims 4 to 9 in a battery.
Citation Information
Patent Citations
Zr / Ga doped halide solid electrolyte coated high-nickel positive electrode material and preparation method thereof
CN117673297A
Composite solid electrolyte and solid-state battery thereof
CN118315572A